(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This study shows the legal-labour implications of bankruptcy cases under the new regulations. It specifically deals with the key role played by the new commercial law judges to settle labour matters, the effects that the declaration of bankruptcy have on business and the work-related activity of employees, the influence that the declaration on work-related loans taken out before and after said declaration has, as well as that of the working conditions and collective labour relations.